Sequential Docetaxel in ≥7 Cycles Followed by Cabazitaxel Improves Oncological Outcomes in Patients with Metastatic Castration-Resistant Prostate Cancer - Seiichi Kato; Manabu Takai; Koji Iinuma; Shota Fujimoto; Masahiro Nakano; Takashi Ishida; Masahiro Uno; Masayoshi Tamaki; Mitsuhiro Taniguchi; Hisao Komeda; Yoshito Takahashi; Takuya Koie (The Scientific World Journal)
Background. Docetaxel (DOC) was the first regimen that increased the survival and became the standard-of-care in patients with metastatic castration-resistant prostate cancer (mCRPC). However, it is unclear whether switching to second-line chemotherapy or optimal sequencing of cabazitaxel (CBZ) ensures better clinical outcomes. We aimed to evaluate the efficacy of sequential therapy with DOC and CBZ and the effect of the number of prior DOC cycles on oncological outcomes in patients with mCRPC. Methods. We retrospectively included 46 mCRPC patients who received DOC followed by CBZ at quaternary hospitals in Japan between February 2015 and March 2019. Participants received intravenous DOC (40–75 mg/m2) every 3–4 weeks; CBZ (15–25 mg/m2) was administered every 3–4 weeks. Androgen-deprivation therapy and prednisolone 5 mg (twice daily) were administered throughout both regimens. The primary endpoints were overall (OS) and progression-free survival (PFS). The secondary endpoints were the rates of ≥30% and ≥50% reduction in prostate-specific antigen (PSA) levels at chemotherapy initiation. Results. Participants were divided into two groups according to DOC cycles (Groups A and B: ≤6 and ≥7 DOC cycles, respectively). The rates of ≥30% and ≥50% reduction in PSA levels were higher in Group B than in Group A, but there were no significant differences in both groups. Median OS in Groups A and B was 12.7 and 71.0 months, respectively P<0.001; median PFS in Groups A and B was 3 and 12 months, respectively P<0.001. Conclusions. Administration of ≥7 cycles of DOC followed by CBZ may improve oncological outcomes in patients with mCRPC.